Critical intermediate β‐Li2NiO3 phase for structural degradation of Ni‐rich layered cathodes during thermal runaway. Issue 1 (6th January 2023) - Gao, Ang; Li, Xinyan; Zhang, Qinghua; Lyu, Yingchun; Tang, Zhexin; Shang, Tongtong; Meng, Fanqi; Luo, Yanhong; Ji, Pengxiang; Wang, Xuefeng; Xiao, Dongdong; Su, Dong; et al.
Abstract: Ni‐rich layered (NRL) cathodes have been widely considered to undergo a degeneration from layered to spinel‐like phases and finally to a rock−salt phase, which jeopardizes the battery's performance and safety. However, this process does not sufficiently explain the drastic structure collapse that occurs during thermal runaway, as the lattice constants of these structures are similar. Herein, an intermediate β‐Li2 NiO3 phase is identified during the thermally driven structural evolution via in situ heating scanning transmission electron microscopy imaging. The antihoneycomb‐ordered structure leads to a larger lattice mismatch of up to ∼15% with the layered structure. The resulting strain triggers huge bulk stress and the labile oxygen of the β‐Li2 NiO3 phase aggravates the oxygen release, severely reducing the thermal stability of NRL materials. Finally, based on the screening for 3d transition metals, doping elements are chosen to suppress the β‐Li2 TMO3 phase and enhance thermal stability. The findings provide comprehensive insights into the structural degradation process of NRL materials and pave the way to design high‐performance and safe battery systems. Abstract : In thermal degradation of Ni‐rich layered (NRL) cathodes, we first find the intermediate β‐Li2 NiO3 phase causes the large lattice mismatch and bulk stress, accounting for the poor thermal stability of NRL materials. Then, the thermodynamic stability of the β‐Li2 NiO3 phase is discussed for pointing out the future design of high‐performance and safe NRL cathodes.